Creative Knowledge: The Centrality of Creativity in Teachers' Conceptions of Subject English - Frawley, Emily (Changing English, 2020)
This paper examines the notion of creativity as a core concept in English teachers' knowledge and valuing of their subject. It draws on research from a broader investigation into teachers as writers and discusses one of the key findings of the study: that creativity is not only crucial to how teachers approach their pedagogy and subject content, but that contexts in which creativity is minimised in English teachers' lives results in struggle or even a departure from the profession. The paper concludes with a call for teachers and bureaucrats to affirm creative knowledge as foundational to English teachers and their profession, and the ability of teacher narratives to offer a powerful contribution to debates in English teaching.